The Role of Education and Skills in Increasing Women's Participation in Population Policy - Usman, Musrayani; Muhammad, Rahmat; ., Hasbi; ., Mario; Lestari, Arini Enar (KnE Social Sciences, 2024)
Women’s participation in population policy has an important role to play in achieving the sustainable development goals. Education and skills are key factors influencing women’s participation rates in population policy. This study aims to explore the role of education and skills in increasing women’s participation in population policy and analyze its impact on sustainable development. This research method uses a qualitative approach by conducting a literature review and analysis of relevant population policies as well as several interviews. Data collection is carried out through literature studies, government reports, and related policy documents. The results show that education has an important role in increasing access to information and knowledge needed in decision-making related to population policy. In addition, education also provides the skills and abilities needed to be actively involved in the process of planning and implementing population policy. In addition to education, skills also have a significant role in increasing women’s participation in population policy. Effective communication and leadership are essential in influencing the successful implementation of population policy. Therefore, education and skills have an important role in increasing women’s participation in the population policy. To achieve sustainable development, it is important to strengthen the efforts to improve women’s access to relevant education and skills training, and strong and inclusive policy support measures also need to be provided to encourage women’s participation in decision-making related to population policy. Keywords: the role of education, skills, women’s participation, population policy